Could edaravone prevent gentamicin ototoxicity? An experimental study. (February 2017) - Turan, M; Ciğer, E; Arslanoğlu, S; Börekci, H; Önal, K
Objectives: Clinical application of gentamicin may cause nephrotoxicity and ototoxicity. Our study is the first study to investigate the protective effects of edaravone against the gentamicin-induced ototoxicity. We investigated the protective effect of intraperitoneal (i.p.) edaravone application against gentamicin-induced ototoxicity in guinea pigs. Methods: Fourteen guinea pigs were divided into two equal groups consisting of a control group and a study group. One-hundred sixty milligrams per kilogram subcutaneous gentamicin and 0.3 mL i.p. saline were applied simultaneously once daily to seven guinea pigs in the control group (group 1). One-hundred sixty milligrams per kilogram gentamicin was applied subcutaneously and 3 mg/kg edaravone was applied intraperitoneally once daily for 7 days simultaneously to seven guinea pigs in the study group (group 2). Following the drug application, auditory brainstem response measurements were performed for the left ear on the 3rd and 7th days. Results: Hearing threshold values of the group 1 and group 2 measured in the 3rd day of the study were detected as 57.14 ± 4.88 and 82.86 ± 7.56, respectively. This difference was statistically significant ( p < 0.05). Hearing threshold values of the group 1 and group 2 measured in the 7th day of the study were detected as 87.14 ± 4.88 and 62.86 ± 4.88, respectively. This difference was statistically significant ( p < 0.05). Conclusion: A statistically significant difference between the average threshold values of edaravone-administered group 2 and that of group 1 without edaravone was found. These differences show that systemic edaravone administration could diminish ototoxic effects of gentamicin and the severity of the hearing loss.